OPTIMASI DEASETILASI KHITIN DARI KULIT UDANG DAN CANGKANG KEPITING LIMBAH RESTORAN SEAFOOD MENJADI KHITOSAN MELALUI VARIASI KONSENTRASI NaOH - N. M. Puspawati; I N. Simpen (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2010)
Chitin resulted from treatment of shrimp and crab shells wasted of seafood restaurant, can be transformedinto chitosan through deacetylation process using concentrated NaOH. This research aims to investigate the optimumcondition of the deacetylation process to achieve a high yield and deacetylation degree of chitosan by varying theconcentration of NaOH while temperature and length of reaction are made constant at 120oC for 4 hours. Theconcentration of NaOH used in this research was 50; 55; and 60%, respectively. All chitosan obtained were purifiedand characterized by FTIR. The deacetylation degree of chitosan was calculated based on FTIR spectra data.The result found, the optimum condition for deacetylation of chitin from shrimp shells at 120oC for 4hours, was achieved using NaOH 60%, giving a high yield of 54.90% and deacetylation degree of 88.04%.. Usingthe same condition as for deacetylation chitin from shrimp, chitosan obtained from crab shells gave a better yieldwhich was 62.76 %, and the deacetylation degree of 88.53%. Both chitosans obtained from shrimp and crab shellssolubled in a 2% acetic acid solution.